Intrathoracic Nissen’s fundoplication. Gastric perforation with gastro-pleural fistula. - Delgado, Bolívar; Bowley, Hilmer; Martínez, José L; Chifflet, Juan (Cirugía del Uruguay, 1983)
... Two cases of gastro-pleural fistula with fatal evolution are presented. They complicated a Nissen 's fundoplication performed for peptic stricture due to gastro-esophageal reflux. Possible pathogenetic factors and frequency of this serious complication are consideréd.